High-throughput methods to identify male Cannabis sativa using various genotyping methods - Anthony Torres; Christopher Pauli; Robert Givens; Jason Argyris; Keith Allen; Amparo Monfort; Reginald J. Gaudino (BMC, 2022)
Abstract Background Cannabis sativa is a primarily dioecious angiosperm that exhibits sexual developmental plasticity. Developmental genes for staminate male flowers have yet to be elucidated; however, there are regions of male-associated DNA from Cannabis (MADC) that correlate with the formation of pollen producing staminate flowers. MADC2 is an example of a PCR-based genetic marker that has been shown to produce a 390-bp amplicon that correlates with the expression of male phenotypes. We demonstrate applications of a cost-effective high-throughput male genotyping assay and other genotyping applications of male identification in Cannabis sativa. Methods In this study, we assessed data from 8200 leaf samples analyzed for real-time quantitative polymerase chain reaction (qPCR) detection of MADC2 in a commercial testing application offered through Steep Hill Laboratories. Through validation, collaborative research projects, and follow-up retest analysis, we observed a > 98.5% accuracy of detection of MADC2 by qPCR. We also carried out assay development for high-resolution melting analysis (HRM), loop-mediated isothermal amplification (LAMP), and TwistDx recombinase amplification (RPA) assays using MADC2 for male identification. Results We demonstrate a robust high-throughput duplex TaqMan qPCR assay for identification of male-specific genomic signatures using a novel MADC2 qPCR probe. The qPCR cycle quotient (Cq) value representative of MADC2 detection in 3156 males and the detection of tissue control cannabinoid synthesis for 8200 samples and the absence of MADC2 detection in 5047 non-males demonstrate a robust high-throughput real-time genotyping assay for Cannabis. Furthermore, we also demonstrated the viability of using nearby regions to MADC2 with novel primers as alternative assays. Finally, we also show proof of concept of several additional commercially viable sex determination methodologies for Cannabis sativa. Discussion In industrial applications, males are desirable for their more rapid growth and higher quality fiber quality, as well as their ability to pollinate female plants and produce grain. In medicinal applications, female cultivars are more desirable for their ability to produce large amounts of secondary metabolites, specifically the cannabinoids, terpenes, and flavonoids that have various medicinal and recreational properties. In previous studies, traditional PCR and non-high-throughput methods have been reported for the detection of male cannabis, and in our study, we present multiple methodologies that can be carried out in high-throughput commercial cannabis testing. Conclusion With these markers developed for high-throughput testing assays, the Cannabis industry will be able to easily screen and select for the desired sex of a given cultivar depending on the application.